INOVASI EKSTRAK DAUN KELOR UNTUK MENINGKATKAN GIZI BALITA STUNTING: TRANSFORMASI PENGELOLAAN DATA ADMINISTRASI POSYANDU UNTUK SOLUSI GIZI SEHAT - Riansih, Chici; Yani Noor, Ahmad; Nur Seha, Harinto; Purwanti, Ratih (Permata Indonesia, 2024)
Background: Stunting is a serious health problem in Indonesia that has long-term effects on children under five. Moringa leaf extract, rich in nutrients, could be a potential solution to improve under-five nutrition. In addition, conventional Posyandu data management limits the effectiveness of monitoring. The purpose of this activity is to improve the nutrition of stunted toddlers through moringa leaf extract and transform Posyandu data management with a digital system in Barukan Village, Manisrenggo, Klaten, Central Java. method: The activity was conducted on October 21, 2024 in Barukan Village, Klaten, with education and training for 55 health cadres and 1 village midwife. The results showed that moringa extract improved the nutritional status of children under five and reduced the prevalence of stunting, while the digital system facilitated monitoring and reporting. In conclusion, the combination of moringa extract and digital transformation proved effective in tackling stunting and can be scaled up across Indonesia.